Ruralité, ethnicité et montagne : - Anne-Laure Amilhat Szary (Revue de Géographie Alpine)
In a Latin American context where indigenous populations have had to wait until the end of the XXth century to recover a certain visibility, the definition of Andean identity is still an issue. In this paper, an analysis of the various steps in a territorially based collective movement provides insights into this identity that was for so long denied or repressed on account of socio-political conditions. The possible re-assertion of “Andeanity” is very complex, as the case study of the “Aymaras Sin Fronteras” (Aymaras without borders) movement reveals. In this movement, the territorialisation process is based on the dialectics between its rural, ethnic and mountain (Andean) components.